Phytochemical Analysis and Antioxidant Potential of the Phytonutrient-Rich Decoction of Cichorium spinosum and C. intybus - Brieudes, Vincent; Angelis, Apostolis; Vougogiannopoulou, Konstantina; Pratsinis, Harris; Kletsas, Dimitris; Mitakou, Sofia; Halabalaki, Maria; Skaltsounis, Leandros A. (Planta Medica, 2016)
The Cretan diet, as the basis of the Mediterranean diet, has provided traditional remedies for the general well being of people through the long-established consumption of cooked wild greens and vegetables. The intake of the water decoctions of Cichorium spinosum and Cichorium intybus in the context of the daily dietary regime in Greece has been long associated with “liver detoxifying” properties. In the current study, we performed an in-depth investigation of the water decoctions traditionally prepared from C. spinosum and C. intybus through qualitative UHPLC-HRMS profiling and direct quantification of cichoric and caftaric acid as major antioxidant components of the decoction. In addition, we developed a one-step countercurrent chromatography method for the isolation of the two phenolic acids, along with a sulfoconjugate sesquiterpene lactone present only in the Cretan C. spinosum. All water decoctions were found not to be cytotoxic in human fibroblasts, whereas they all significantly reduced the intracellular reactive oxygen species, which is consistent with the major presence of strong antioxidant compounds such as cichoric acid. This work demonstrates that the intake of these decoctions in doses suggested by Greek traditional use is comparable to the ingestion of a phytomedical preparation of antioxidants. These results contribute to our current knowledge on the beneficial health effect of the Cretan diet.
Keywords: Cichorium spinosum; Cichorium intybus; Asteraceae; cichoric acid; caftaric acid; stamnagathi; Cretan and Mediterranean diet; ROS reduction